An analysis of the procedural features in instituting preliminary hearing in a criminal case - D. Zh. Suyunova (Law and Safety)
The introduction of the institution of preliminary hearing into the criminal procedural legislation determines the ability of the court to prepare a criminal case for the main hearing in order to eliminate the gaps made by the preliminary investigation authorities. In this context, the article analyzes the changes in the national criminal procedural legislation concerning the institution of the preliminary hearing in a criminal case; analyzed foreign experience of individual countries on this topic; the essence and objectives of this institution are determined, some features of its effective enforcement are discussed.